People or place? Neighborhood opportunity influences community garden soil properties and soil-based ecosystem services. Issue 1 (1st January 2018) - Egerer, Monika H.; Philpott, Stacy M.; Liere, Heidi; Jha, Shalene; Bichier, Peter; Lin, Brenda B.
ABSTRACT: Soils are the foundation for cultivating ecosystem services in urban agriculture. Yet, variations in socio-environment characteristics of urbanization leads to variable soil properties and unequal distribution of ecosystem services like soil fertility. Thus, examining relationships among biophysical features and social dimensions of urban agricultural systems is necessary to understand soil functioning variation and to develop urban agricultural systems that promote equitable ecosystem service provisioning. In 25 urban community gardens in California, we examined two links between soil properties and neighborhood socio-demographics: (1) how groundcover management affects soil properties; and (2) how socio-demographics (and in particular, social advantage) can affect groundcover management and soil properties. We found that mulch groundcover improves soil fertility and water holding capacity in gardens, and that socio-demographic factors may affect people's access to mulch to affect soil properties: neighborhoods with measures of higher mobility (e.g., greater vehicle availability), but measures of poorer public/environmental health (e.g., poorer health care access) had more soil organic matter, higher soil nutrient content, and greater water holding capacity. However, we found indicators of high functioning soils in the absence of mulch, indicating that other factors like social networks and organizational support may be important for urban agricultural ecosystem services.